Effect of Citric Acid and Polyvinylpyrrolidone (PVP) on Browning of Kepel (Stelechocarpus burahol (Blume) Hook.f. & Thomson) Nodes - Marendeng, Yunita Kendek; Viorenta, Miranda Gardha; Sinaga, Meisi Olivia; Christy, Nita Elvira; Sibarani, Devi Sonti; Restiani, Ratih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Browning is a major constraint in in vitro propagation of Kepel (S. burahol). Therefore, the selection of an effective anti-browning compound can be useful to prevent browning in Kepel in vitro culture and produce explants that are able to regenerate. This study was aimed to investigate the effect of the addition of citric acid and PVP at different concentrations and incubation conditions on the prevention of browning in in vitro cultures of S. burahol. This research is an experimental study using S.burahol node explants. The research design used a Completely Randomized Design (CRD) with citric acid and PVP treatments of 300 and 400 ppm respectively and control incubated in dark and light conditions. Each treatment was repeated twice. The culture was incubated for 28 days. Observations were conducted on browning initiation time, browning intensity and callus initiation time. Data were analyzed descriptively. The results showed that citric acid treatment of 300 and 400 ppm and incubation of cultures in dark conditions effectively reduced the intensity of browning (0.2) and browning initiation time (6 DAI). In addition, the suplementation of 400 ppm citric acid and incubation in light conditions was also effective in initiating the fastest callus at 2 DAI. The results suggest that the addition of citric acid at concentrations of 300 and 400 ppm is more effective at slowing browning and reducing browning intensity for S. burahol node explants than PVP. The results of this study play an important role in supporting efforts to increase the productivity of S. burahol nodes growth through in vitro culture.